Head and Neck Cancer - An Overview - Hussain, QM; Mahbub-Ul-Alam, M (TAJ: Journal of Teachers Association, 2009)
Head and neck cancers encompass a diverse group of uncommon tumors that frequently are aggressive in their biological behaviors. Some new treatments are available, as are new ways of combining old treatments. doi: 10.3329/taj.v20i1.3098 TAJ 2007; 20(1): 87-90